2015
DOI: 10.3390/f6114059
|View full text |Cite
|
Sign up to set email alerts
|

Forest Parameter Prediction Using an Image-Based Point Cloud: A Comparison of Semi-ITC with ABA

Abstract: Image-based point clouds obtained using aerial photogrammetry share many characteristics with point clouds obtained by airborne laser scanning (ALS). Two approaches have been used to predict forest parameters from ALS: the area-based approach (ABA) and the individual tree crown (ITC) approach. In this article, we apply the semi-ITC approach, a variety of the ITC approach, on an image-based point cloud to predict forest parameters and compare the performance to the ABA. Norwegian National Forest Inventory sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…The abovementioned studies applying DSI have mainly focused on predicting the forest inventory attributes at a plot or grid level comparable to ABA [34]. However, recent research has also utilized individual tree detection from DSI [35][36][37]. St-Onge et al [35] compared tree detection and tree-level height estimates based on DSI to ALS, and obtained similar results with both data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned studies applying DSI have mainly focused on predicting the forest inventory attributes at a plot or grid level comparable to ABA [34]. However, recent research has also utilized individual tree detection from DSI [35][36][37]. St-Onge et al [35] compared tree detection and tree-level height estimates based on DSI to ALS, and obtained similar results with both data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed lower accuracies as the relative RMSE with ITC was 41.73% and 47.64% with spectral features and vegetation indices, respectively, and with semi-ITC the corresponding values were 46.68% and 51.95%. In [72] the relative RMSE was 26% for quadratic mean diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Especially with ITC and spectral features, we were able to obtain similar results for deciduous trees (relative RMSE 89.07%) to theirs (relative RMSE ranging from 42.00% to 81.98%). In [72], photogrammetric point clouds were utilized to predict total stem volume and stem number at plot level with semi-ITC. The relative RMSE was 46% for stem density, but it was 25% and 30% for volume estimates depending on modelling technique (i.e., multivariate or univariate kNN).…”
Section: Discussionmentioning
confidence: 99%
“…This systematic error can be considerably reduced with the semi-ITC approach as demonstrated in our study. Comparing the semi-ITC and ABA inventory approaches, Breidenbach et al and Rahlf et al [37,61] showed that the semi-ITC approach provided prediction accuracies that were higher or similar to the ABA, while in the study of Ørka et al [23], the ABA performed better than the semi-ITC approach. Based on a trade-off between the goodness of fit and the systematic error, the compared total and species-specific results suggest that the semi-ITC approach in total outperformed the other approaches.…”
Section: Discussionmentioning
confidence: 99%